I want to take you higher the life and times of Sly & the Family Stone - Kaliss, Jeff (Backbeat Books, 2024)
"An account of the rise and fall of rock group Sly & the Family Stone, discussing hit songs such as "I Want to Take You Higher" and "Family Affair," drawing from interviews with band members, managers, and eyewitnesses to show how the band was undermined by drugs and self-delusion, and discusses Sly Stone's comeback concerts"
"Originally published by Backbeat Books in hardcover in 2008, and in a revised paperback edition in 2009"
Keywords: Sly & the Family Stone -- Musikgruppe; Geschichte; Stone, Sly; Sly & the Family Stone (Musical group); Rock musicians / United States / Biography; Rock groups / United States; MUSIC / History & Criticism; Music; Music reviews & criticism; History: specific events & topics; Biographies; Biografie